Exploring the therapeutic potential of 18β-Glycyrrhetinic acid in pulmonary arterial hypertension by integrating network pharmacology and experimental validation - Wenli Yang; Long Ma; Meidong Si; Fang Zhao; Ru Zhou (Journal of Functional Foods)
Background: Pulmonary arterial hypertension (PAH) is characterized by elevated pressure in the pulmonary arteries and can result in right heart failure and possible death.18β-Glycyrrhetinic acid (18β-GA), a beneficial substance found in licorice, shows great potential for medicinal use. Through network pharmacology and experimental validation, this study examined the probable mechanism of 18β-GA in treating PAH. Methods: The analysis of the potential pharmacological activities of 18β-GA was conducted using the network pharmacology method. The network of interactions between proteins was created by identifying shared targets of 18β-GA and PAH across multiple databases. Pathway enrichment was then conducted to determine the key targets. Validation of the interactions between 18β-GA and key targets was performed by molecular docking. Ultimately, we confirmed the modes of operation by utilizing a monocrotaline (MCT)--induced PAH model in rats. Results: A total of 197 potential targets for 18β-GA and 1713 potential targets associated with PAH were successfully identified. Of these, 79 targets were identified as common to both 18β-GA and PAH. Through the analysis of the PPI network, identified key targets, including IL6, AKT1, ALB, BCL2, NFKB1, IL1B, SRC, MMP9, PPARG, MAPK3, PTGS2, ESR1, TNF, CTNNB1 and CASP3. Furthermore, the analysis of molecular docking indicated that SRC exhibited the highest affinity for 18β-GA. The efficacy of 18β-GA in mitigating the advancement of MCT-induced PAH in rats was proven by in vivo investigations. Conclusions: This study presents initial findings about the molecular mechanism by which 18β-GA exerts its therapeutic effects on PAH. The findings suggest that using 18β-GA for treating PAH may involve the deactivation of SRC and the reduction of oxidative stress.